The Autofictional - Effe, Alexandra,Lawlor, Hannie (Springer International Publishing, 2022)
1 Introduction: From Autofiction to the Autofictional; Alexandra Effe and Hannie Lawlor – 2. Five Theses on Autofiction/the Autofictional; Martina Wagner-Egelhaaf – 3. The Fictional in Autofiction; Alison James – 4. A Cognitive Perspective on Autofictional Writing, Texts, and Reading; Alexandra Effe and Alison Gibbons – 5. The Pragmatics of Autofiction; Arnaud Schmitt – 6. The Autofictional in Serial, Literary Works; Ricarda Menn and Melissa Schuh – 7. Metanarrative Autofiction: Critical Engagement with Cultural Narrative Models; Hanna Meretoja – 8. Multilingual Autofiction: Mobilizing Language(s)?; Helle Egendal – 9. Visual Autofiction: A Strategy for Cultural Inclusion; Karen Ferreira-Meyers and Bontle Tau – 10. Autofiction, Post-conflict Narratives, and New Memory Cultures; Hywel Dix – 11. Autofiction as a Lens for Reading Contemporary Egyptian Writing; Hala Kamal, Fatma Atef Massoud, and Zainab Magdy – 12. Autofiction and Film: Archival Practices in Post-Millennial Documentary Cinema in Argentina and Spain; Anna Forné and Patricia López-Gay – 13. Autofiction and Shishōsetsu: Women Writers and Reinventing the Self; Justyna Kasza.-14. Autofiction and the Diary: The Radicalization of Autofiction in works by Hervé Guibert and Christine Angot; Sam Ferguson.-15. Autofiction and Self-Portraiture: Jenny Diski and Claude Cahun; Ben Grant – 16. Visual Autofiction: A Strategy for Cultural Inclusion Autofiction and Photography: “The Split of the Mirror”; Laura Marcus. This open access book offers innovative and wide-ranging responses to the continuously flourishing literary phenomenon of autofiction. The book shows the insights that are gained in the shift from the genre descriptor to the adjective, and from a broad application of “the autofictional” as a theoretical lens and aesthetic strategy. In three sections on “Approaches,” “Affordances,” and “Forms,” the volume proposes new theoretical approaches for the study of autofiction and the autofictional, offers fresh perspectives on many of the prominent authors in the discussion, draws them into a dialogue with autofictional practice from across the globe, and brings into view texts, forms, and media that have not traditionally been considered for their autofictional dimensions. The book, in sum, expands the parameters of research on autofiction to date to allow new voices and viewpoints to emerge.
10.1007/978-3-030-78440-9
Keywords: Historiography.; Comparative literature.; Literature—Philosophy.; Literature.; Collective memory.